IMPROVING SPEAKING SKILL BY USING MODELING STRATEGY SECOND SEMESTER OF ELECTRO MAJOR STUDENTS AT SEKOLAH TINGGI TEKNIK MALANG - Akhmad Sidiq (Sekolah Tinggi Teknik Malang, 2015)
This research is categorized as a classroom action research (CAR). This research proposed to improve the speaking skill of university students by using modeling strategy in the teaching English at the second semester students of Sekolah Tinggi Teknik Malang to solve the students’ incompetency on speaking skill. Based on the researcher’s experience as a lecture and the results of preliminary research, it was revealed that the students were not confident to speak English, because they were shy to speak English due to the lack vocabulary and fluency, they hesitated to speak English because they thought that their English was not good enough. The result of the research showed that the criteria of success had been reached. There were two aspects determined as the success criteria of the implementation of group investigation in the teaching speaking; score improvement and classroom atmosphere (motivation). The result of speaking test presented that the students had made some progress. In the first cycle, average score was 7.42. It meant that the research was successful so the research stopped.